Product Placement: Enclosing of Culture and Commerce in Modern Russian Cinema - ЗемкоМария Алексеевна (Journal of Economic Sociology, 2010)
The paper describes how the market meets culture in modern Russian cinema through the technologies of product placement. Interpreting data of the expert interviews and using content analysis of modern Russian blockbusters, the author reveals peculiarities of product placement in contemporary Russian cinema. Commercialisation of domestic film production industry is also analysed.product placement